Right Atrial Perforation Secondary to Implantable Cardioverter Defibrillator Insertion - Nam T Tran; Adam Zivin; Darius Mozaffarian; Riyad Karmy-Jones (Canadian Respiratory Journal)
Implantable cardioverter defibrillator (ICD) placements can be associated with serious complications. This paper reports a patient in whom percutaneous placement of an ICD resulted in a hemopneumothorax. This was due to an active fixation lead that perforated the right atrial wall and injured the adjacent lung parenchyma. The hemothorax was drained thoracoscopically, and the atrial injury was covered with fibrin glue.